Beliefs about Teaching Geometric Transformations with Geometers’ Sketchpad: A Reflexive Abstraction - Belbase, Shashidhar (Journal of Education and Research, 2013)
A teacher’s belief plays a significant role in the quality of teaching mathematics. In a fictive way, I changed my role from a researcher to a research participant in an imaginative interview. My interior other (David) interviewed me as a researcher. A single interview session was held lasting for about three hours. The interview text was used for the analysis and interpretation using the grounded theory method. I invented a substantive theory of my beliefs about teaching geometric transformations with Geometer’s Sketchpad. The theory is “reflexive abstraction of my beliefs about teaching Geometric Transformations with Geometer’s Sketchpad” as a personal theory characterized by some basic categories of - beliefs about the advancement of pedagogy, beliefs about pedagogical environment, beliefs about the role of students’ and teacher, beliefs about self as a future teacher, beliefs about teaching learning activities, and beliefs about transitions in teaching learning. I reconstructed a synthesis of the characteristics of these beliefs. While constructing these layers of interpretive accounts, I used radical constructivist grounded theory as a theoretical base. DOI: http://dx.doi.org/10.3126/jer.v3i2.8396 Journal of Education and Research August 2013, Vol. 3, No. 2, pp.15-38